A new species in the Fejervarya limnocharis species complex (Amphibia: Dicroglossidae) - Tong, Haojie; Wang, Kaixin; Xu, Jun; Guo, Junru; Guo, Yaxin; Shi, Shuangyue; Jin, Yuanting (Zootaxa, 2025)
The Fejervarya limnocharis is a dicroglossid species complex distributed across east and southeast Asia, comprising four species. We previously found populations from Zhoushan Archipelago should be a distinct species with independent evolutionary history, through systematic classification based on mitochondrial DNA (mtDNA) and eight nuclear DNA loci, belonging to the fifth species in the complex. In this study, we described this new species as Fejervarya zhoushanensis sp. nov. by further comparing its genetic and morphological characteristics with its sister lineage F. kawamurai. The new species exhibited distinct genetic differences, as evidenced by genomic single nucleotide polymorphism (SNP) data. Morphological distinctions include larger snout-to-vent length (SVL), longer head length (HL), larger eye diameter (ED), greater distance between aeddistance anterior eye corners (AED), longer forearm length (FLL) and foot length (FL). Additionally, males exhibited larger tympanum diameter (TD), snout length (SL) and inner metatarsal tubercle length (IMTL); while females showed longer hindlimb length (HLL). These differences enabled clear taxonomic separation between F. zhoushanensis sp. nov. and F. kawamurai.